2017
DOI: 10.18203/2320-6012.ijrms20174552
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ adherence to antimalarial medication; self-report of patients at the Volta regional hospital of Ho, Ghana

Abstract: Background: Despite the advancement in malaria treatments and management; malaria morbidity and mortality is still on the increase. This phenomenon has been mostly attributed to the emergence and transmission resistance of the plasmodium parasite to drugs; which is as a result of non-adherence to anti-malaria medication. Therefore, the purpose of this study was to assess patients’ adherence to anti-malarial medications and the factors influencing their adherence in the Volta regional hospital.Methods: A descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 22 publications
3
10
2
Order By: Relevance
“…Also, some of the studies were conducted using children to assess their adherence level [ 24 , 30 ]. One can therefore stipulate that whereas children can be monitored by their parents to ensure strict adherence to antimalarial medication, contributing to higher adherence level, adults might not strictly adhere to treatment due to schedules and other related factors [ 21 ]. The current study found the educational status of respondents to be statistically related to patients' adherence to ACT with p value of 0.003.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Also, some of the studies were conducted using children to assess their adherence level [ 24 , 30 ]. One can therefore stipulate that whereas children can be monitored by their parents to ensure strict adherence to antimalarial medication, contributing to higher adherence level, adults might not strictly adhere to treatment due to schedules and other related factors [ 21 ]. The current study found the educational status of respondents to be statistically related to patients' adherence to ACT with p value of 0.003.…”
Section: Discussionmentioning
confidence: 99%
“…Deportee et al and Fogg et al defined adherent patients as those who reported having taken the treatment as recommended (regarding timing and dosage) with no tablets remaining [ 9 , 10 ]. Several studies have reported patient adherence to ACT across Africa [ 9 21 ], but adherence levels varied from less than 30% for ACT in Kenya [ 22 ] up to 100% adherence to ACT in Malawi [ 23 ]. A recent study by Afaya et al reported an adherence level of ACT by patients in the Volta Regional Hospital, Ghana, to be 36.6% [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations